Environmental and health education for school-age children: a transdisciplinary approach - Schall Virginia T. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1994)
A brief critical analysis and suggestion for guidelines concerning environmental and health education in the elementary school are presented from the viewpoint of emerging pedagogic experiences and theoretical philosophical reflections. The major points discussed are: the importance of transdisciplinarity, the enhancement of participatory education where technical knowledge and popular wisdom meet, the planning and execution of concrete experiences which stimulate the sensations of pleasure and of admiration for nature and life, the analysis and the search for a solution to problems affecting the local reality of pupils without losing sight of global issues. A major priority is investment in teacher training, stimulating acquisition of knowledge through creative practice and formation of a critical awareness, essential for the school to clearly show its commitment to a future of greater social equality and harmony in our relationship to the environment.